2004
DOI: 10.1042/cs20040122
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temporal QT variability index in patients with chronic renal failure

Abstract: Patients with CRF (chronic renal failure) are at increased risk of cardiovascular diseases, and 60% of cardiovascular mortality in CRF is attributed to sudden death. Various abnormalities in myocardial repolarization are associated with the risk of ventricular arrhythmia. The aim of this study was to evaluate an index of temporal myocardial repolarization lability, the temporal QTVI (QT variability index), in patients with CRF. ECGs were recorded in 153 patients with CRF on haemodialysis (n=67), continuous amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
8
2
1
Order By: Relevance
“…36 Johnsson et al reported that Qtvi was increased by 47% in 153 patients with advanced CKD (43 individuals with stage 4 CKD, 67 patients undergoing hemodialysis, and 43 patients on CaPD) during a 30 min rest period compared with 39 age-matched healthy controls. 35 the Qtvi was similar in patients with stage 4 CKD and in those on dialysis, whereas it was higher in patients with diabetes compared with nondiabetic patients with renal failure. 35 Furthermore, in a multiple linear regression analysis, a history of diabetes or coronary artery disease were the only independent predictors of Qtvi in patients with advanced CKD.…”
Section: Epidemiologycontrasting
confidence: 47%
See 3 more Smart Citations
“…36 Johnsson et al reported that Qtvi was increased by 47% in 153 patients with advanced CKD (43 individuals with stage 4 CKD, 67 patients undergoing hemodialysis, and 43 patients on CaPD) during a 30 min rest period compared with 39 age-matched healthy controls. 35 the Qtvi was similar in patients with stage 4 CKD and in those on dialysis, whereas it was higher in patients with diabetes compared with nondiabetic patients with renal failure. 35 Furthermore, in a multiple linear regression analysis, a history of diabetes or coronary artery disease were the only independent predictors of Qtvi in patients with advanced CKD.…”
Section: Epidemiologycontrasting
confidence: 47%
“…35 the Qtvi was similar in patients with stage 4 CKD and in those on dialysis, whereas it was higher in patients with diabetes compared with nondiabetic patients with renal failure. 35 Furthermore, in a multiple linear regression analysis, a history of diabetes or coronary artery disease were the only independent predictors of Qtvi in patients with advanced CKD. 35 the elevated Qtvi in patients with advanced CKD was the result of both reduced rr interval variance (secondary to reduced autonomic control of heart rate) and increased Qt-interval variance.…”
Section: Epidemiologycontrasting
confidence: 47%
See 2 more Smart Citations
“…9,10 Pada penderita PGK terdapat pemanjangan QTVI yang bermakna bila dibandingkan dengan kontrol sehat. 11 Angka kejadian aritmia fatal dan kematian jantung mendadak pada penderita PGK meningkat seiring dengan makin rendahnya laju filtrasi glomerulus. 4,6 Hal ini mungkin berhubungan dengan QTVI yang makin panjang sebagai salah satu mekanisme yang mendasarinya, namun belum ada penelitian yang dilakukan untuk membuktikan hal tersebut.…”
Section: Pendahuluanunclassified